Impact of Dosing Conversion From Basal Insulin to Follow-On Insulin Glargine. (April 2021) - Maes, Marina L.; Ashjian, Emily J.; Kippes, Kellie A.; Marshall, Vince; Rida, Nada; Thompson, Amy N.
Background: Several basal insulins have recently come to market including follow-on insulin glargine (Basaglar®). Currently, there is no real-world data published on the implications of conversion to Basaglar on dosing or glycemic control. Objective: To identify differences in basal insulin dosing requirements, hemoglobin A1c (HbA1c), and incidence of hypoglycemia or weight gain when converting a patient to Basaglar from another basal insulin. Methods: Single-center, retrospective chart review at an academic medical center. All patients prescribed Basaglar between December 15, 2016, and August 31, 2017 were included for review if converted from another basal insulin. Primary outcome: Difference in basal insulin requirements in both units/d and units/kilogram (kg)/d after conversion to Basaglar. Secondary outcome: Change in HbA1c and weight. Results: Mean basal insulin dose was 38.4 ± 26.3 units/d pre-conversion and 40.5 ± 29.8 units/d post-conversion (P = .031). Results were significant for patients with type 2 diabetes mellitus (T2DM; pre-conversion basal dose 34.6 ± 24.3 units/d; post-conversion basal dose 37.6± 29.0 units/d; P = .009). Weight-based dosing changed from 0.37 ± 0.25 units/kg/d pre-conversion to 0.39 ± 0.29 units/kg/d post-conversion (P = .056) and was significant for patients with T2DM (P = .040). A nonsignificant decrease in HbA1c was seen (−0.14% ± 1.24%; P = .142). There was no difference seen in weight (111.6 ± 46.3 kg vs 111.7 ± 46.9 kg; P = .662). Conclusion: Patients with diabetes require similar basal insulin doses upon conversion to Basaglar. Clinicians should monitor blood glucose closely during basal insulin transition.